REPOSITORI INSTITUSI MENUNJANG AKREDITASI PROGRAM STUDI - Zulfitri Zulfitri (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2018)
Abstract: The term accreditation is no stranger to educational institutions, especially universities. Accreditation is a comprehensive process of evaluation and assessment of the commitment of tertiary institutions to the quality and capacity of the implementation of tertiary institutions, to determine the appropriateness of programs and educational units. Information systems and facilities that show learning in tertiary institutions and study programs also include the priority assessment of accreditation, including information systems in libraries, one of which is the institutional repository. Institutional repositories are very instrumental in supporting the accreditation of this study program, namely increasing the reputation and ranking of the relevant institutions and increasing the visibility of the writers, especially lecturers of a study program. The ranking of an institution can be measured through a webometrics conducted by The Consejo Superior de Investigaciones Cientificas (CSIS), which is a research institute based in Spain. This ranking is done to show the breadth or affordability of access to a digital repository of a university with its web indicators including global visibility, size, rich files and scientific impact repositories.Keywords: Accreditation, Institutional Repositories, Universities and Study Programs.Abstrak : Istilah akreditasi tidak asing lagi bagi instansi pendidikan, terutama perguruan tinggi. Akreditasi merupakan proses evaluasi dan penilaian secara komprehensif atas komitmen perguruan tinggi terhadap mutu dan kapasitas penyelenggaraan Tridarma perguruan tinggi, untuk menentukan kelayakan program dan satuan pendidikan. Sistem informasi dan fasilitas-fasilitas yang munujang pembelajaran di perguruan tinggi dan program studi juga termasuk prioritas penilaian dari akreditasi, di antaranya sistem informasi di perpustakaan, salah satunya adalah repository institusi. Repositori institusi sangat berperan dalam menunjang akreditasi program studi ini, yaitu meningkatkan reputasi dan peringkat lembaga yang bersangkutan dan meningkatkan visibilitas para penulis terutama dosen dari suatu program studi. Adapun peringkat suatu lembaga dapat diukur melalui webometrik  yang dilakukan oleh The Consejo Superior de Investigaciones Cientificas (CSIS), yaitu lembaga riset yang berkedudukan di Spanyol. Pemeringkatan ini dilakukan untuk menunjukkan keluasan atau keterjangkauan akses repositori digital suatu perguruan tinggi dengan indikator webnya antara lain berupa visibilitas global, size, rich file dan impact repository ilmiah.Kata kunci : Akreditasi, Repositori Institusi, Perguruan Tinggi dan Program Studi.